The effect of temperature variation on the surface hardness of AISI 1045 steel using palm shell media with the pack carburizing method - Murtadhahadi, Murtadhahadi; Syarif, Jenne; Zannun, Zannun (Journal of Mechafa Engineering and Fabrication, 2024)
material for making machine components such as shafts, gears, chisels and bearings in motor vehicles. The use of medium carbon steel in the industrial world is accompanied by adjustments to the required metal conditions, such as the machining process and surface treatment. Pack Carburizing is a process of adding carbon elements or chemical heat treatment which is done by changing the chemical composition of the steel surface by heating at austenite temperature. To obtain maximum pack carburizing results, several processes need to be carried out, namely heating temperature, Holding Time, carbon media and quenching. The purpose of this study was to determine the effect of variations in heating temperature on increasing hardness with the Pack Carburizing heat treatment process. The experimental method used in heat treatment at different temperatures was 850 ° C, 900 ° C, 950 ° C and a holding time of 2 hours. From the results of hardness testing on raw materials, the average hardness value was obtained at 64.20 HRC, after the pack carburizing process the average value at a temperature of 850 °C was 75.93 HRC, and at a temperature of 900 °C it was 88.20 HRC, and at a temperature of 950 °C the highest average value was obtained at 90.23 HRC